243 MEASURED FRAILTY AND POTENTIALLY INAPPROPRIATE PRESCRIBING IN ACUTELY HOSPITALISED OLDER ADULTS: A PROSPECTIVE OBSERVATIONAL STUDY. (18th November 2021) - Randles, M; Gallagher, P; O'Mahony, D
Abstract: Background: Frailty characteristics such as compromised response to stressors and accumulation of deficits in physiological systems may leave frailer older adults at higher risk of adverse outcomes from PIP, compared with their non-frail counterparts of the same age. This study aims to examine the relationship between measured frailty and potentially inappropriate prescribing in older adults presenting acutely to hospital. Methods: A prospective observational study was conducted. Participants were acutely hospitalised older adults. Inclusion Criteria: Age ≥ 65 years old, acute admission <72 hours, expected length of stay >24 hrs. Exclusion Criteria: <65 years of age, actively dying, direct admission to ICU, inability to provide informed consent and next of kin declined consent, patients in isolation for infection control purposes. Medical chart review was carried out, followed by a short interview using a standardised data collection proforma. Frailty was measured using the Clinical Frailty Scale and the Frail-VIG frailty index. Potentially Inappropriate Prescribing was identified using the STOPP/START criteria. Results are presented for the first 200 participants. Results: The mean (±standard deviation [SD]) age of study participants was 79.25[±7.14], 56.5% were female. The prevalence of frailty measured using the CFS and Frail-VIG were 61.5% and 50.5% respectively. Applying the CFS, the mean number of STOPP criteria in non-frail patients was 1.03 and 1.87 for frail patients (p = 0.001 CI 95%) and 1.14 and 2.10 (p = 0.001 CI 95%) using the Frail-Vig Index. Conclusion: Frailty is associated with functional decline, falls, hospitalisation and death. Frail patients had a higher mean number of STOPP criteria. As medication side effects are themselves included as part of the frailty syndrome, in-hospital medication review and patient centred medication optimisation should be guided by patient's frailty status to reduce adverse outcomes.